Democratic Leadership and IMTAQ: Strengthening Islamic Culture at MAN 2 Muaro Jambi, Indonesia - Dinda Atika; M. Gazali; Khairun Najib; Ismail Yau Abubakar (Tuah Foundation, 2025)
Social transformation and technological advancement present significant challenges for madrasah institutions in preserving their Islamic identity and fostering student character development. One strategic approach involves strengthening Islamic culture through effective madrasah leadership and structured developmental programs. This study aims to analyze the role of democratic leadership exercised by madrasah principals in cultivating Islamic culture through the Faith and Piety Program (Program Iman dan Taqwa/IMTAQ) at Madrasah Aliyah Negeri 2 Muaro Jambi, Indonesia. The research employs a descriptive qualitative approach with data collection techniques including in-depth interviews, participant observation, and document analysis. Informants comprise the madrasah principal, teachers responsible for program activities, and selected students. Data analysis was conducted through stages of reduction, presentation, and conclusion drawing. The findings demonstrate that democratic leadership enables active participation of teachers and staff in the planning, implementation, and evaluation of the IMTAQ Program. Core activities include dhuha prayer, congregational dzuhur prayer, recitation of Surah Yasin, religious talks (kultum), and memorization of prayers and short verses, which consistently foster worship discipline and student religiosity. Supporting factors encompass collaboration among all madrasah community members and the availability of worship facilities, while primary obstacles include time constraints and diverse religious backgrounds among students. These findings reinforce the theoretical framework that democratic leadership plays a strategic role in shaping school culture based on Islamic values. Research implications include the necessity of integrating similar programs into national education policy to strengthen Islamic character education, serving as a practical leadership model for other Islamic educational institutions.